Microstructural Characteristics of High Velocity Oxygen Fuel (HVOF) sprayed NiCrBSi-SiC Composite Coating on a Low Alloy Steel - Islak, Serkan; Buytoz, Soner; Kurt, Bülent (6th International Advanced Technologies Symposium (IATS’11), 16-18 May 2011, 13-21, Elazığ,, 2011)
In this study, NiCrBSi-SiC powders were sprayed using a high velocity oxygen fuel technique on AISI 1030 steel substrate. Powder mixtures with different weight mixing ratios, NiCrBSi+10 wt.% SiC, NiCrBSi+20 wt.% SiC and NiCrBSi+40 wt.% SiC coatings were prepared. The deposited coatings are compared in terms of their phase composition, microstructure and hardness. It is proved that the degree of mixing of the NiCrBSi and SiC components in the powder has massive effect on the phase composition, microstructure and hardness of the coatings. The structure and morphologies of Ni-based coatings were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive spectrometer (EDS) and optical microscope (OM). Microstructures of the coatings have been revealed to the presence of a large amount of dispersed Ni and Cr carbide and/or borides in the Ni matrix. Microhardness of the coatings is found to in the range of 550–830 Hv, which is higher than the substrate material
Keywords: HVOF, NiCrBSi-based coating, SiC powder